2020
DOI: 10.2217/fmb-2019-0173
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Stabilized with Propolis Show Reduced Toxicity and Potential Activity Against Fungal Infections

Abstract: Aim: Elucidate the antifungal efficacy of biologically synthesized silver nanoparticles with ethanolic propolis extract (AgNPs PE) against the planktonic forms and biofilms of clinically important fungi. Materials & methods: AgNPs were synthesized, characterized and evaluated for cytotoxicity, mutagenicity and antimicrobial activity. Results: AgNPs PE displayed a colloidal appearance, good stability and size of 2.0–40.0 nm. AgNPs PE demonstrated lower cytotoxicity and nonmutagenic potential. In addition, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…These NPs are the first-choice nanomaterials to be used as nanoantifungals due to their low cost, easy application, eco-friendly characteristics and wide viability [ 1 , 5 ]. They exhibit potential as antifungals [ 29 , 36 , 37 ], besides the other biomedical benefits [ 24 ]. These nanomaterials may have individual particle size dimensions ranging from 1 to 100 nm with aggregate sizes have a higher size range.…”
Section: Nanoantifungals: Diversity and Relevance For Applications In Veterinary Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…These NPs are the first-choice nanomaterials to be used as nanoantifungals due to their low cost, easy application, eco-friendly characteristics and wide viability [ 1 , 5 ]. They exhibit potential as antifungals [ 29 , 36 , 37 ], besides the other biomedical benefits [ 24 ]. These nanomaterials may have individual particle size dimensions ranging from 1 to 100 nm with aggregate sizes have a higher size range.…”
Section: Nanoantifungals: Diversity and Relevance For Applications In Veterinary Medicinementioning
confidence: 99%
“…at very low concentrations (<100 ppm) [ 16 , 60 ] and led to decreased mycotoxin production [ 1 , 61 ]. Also, Kischkel et al [ 37 ] observed the antifungal activity of the AgNPs against C. albicans , F. oxysporum and M. canis .…”
Section: Applications Of Nanoantifungals In Veterinary Medicinementioning
confidence: 99%
“…Silver is one of the noble metals most commonly used to generate NPs due to its unique properties such as chemical stability, good conductivity, and antimicrobial, antiviral, and antifungal potential as well as displaying anti-inflammatory activity (Ahmad et al, 2003 ). Metallic NPs have been widely explored in the literature for their synthesis from biological sources (Dipankar and Murugan, 2012 ; Thangamani and Bhuvaneshwari, 2019 ; Kischkel et al, 2020 ). The synthesis of NPs from plants or microorganisms is possible based on metabolites and proteins present in the extracts.…”
Section: Types Of Nanocarriersmentioning
confidence: 99%
“…have also been widely studied, both against planktonic cells and biofilms (Monteiro et al, 2011 ; Lara et al, 2015 ). Kischkel et al ( 2020 ) evaluated the efficacy of AgNPs carried with propolis extract (PE) against mature biofilms of Candida species and other fungi and observed that the concentration required for the fungicidal activity of the formulation was below the cytotoxic concentration.…”
Section: Current Scenario Of Nanotechnology In the Treatment And Vaccmentioning
confidence: 99%
“…The effects of treatments on the cells were observed at 24 and 48 hours. The assay was performed as described by Kischkel et al (29).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%